Systematic revision of the limestone karst-restricted land snail genus Aenigmatoconcha (Eupulmonata: Helicarionidae), with description of a new species - Pholyotha, Arthit; Sutcharit, Chirasak; Tongkerd, Piyoros; Panha, Somsak (European Journal of Taxonomy, 2021)
Thai limestone karsts are known to contain a rich biodiversity of animals, especially terrestrial snails, but still require further intensive exploration to evaluate their biodiversity. To date, only a few studies on the limestone karst-inhabiting land snail genera have been published. The present work focuses on the species diversity and phylogenetic relationships of the limestone karst-restricted land snail genus Aenigmatoconcha from Thailand, based on comparative morphology and molecular evidence. The results yielded three known species (A. clivicola Tumpeesuwan & Tumpeesuwan, 2017, A. sumonthai Tumpeesuwan & Tumpeesuwan, 2018, and A. mitis (Pfeiffer, 1863) comb. nov.), plus a new species (A. eunetis Pholyotha & Panha sp. nov). The phylogenetic analyses of partial fragments of the mitochondrial cytochrome oxidase c subunit I (COI) gene confirmed the monophyly of all recognized species and congruence with the traditional morphology-based species designations. Average uncorrected p-distances of COI sequences between species were 9.7–12.0% and within species were 0.2–4.2%. This study also provides the re-description of penial sculpture, penial sheath, flagellum, penial caecum, and mantle lobe morphology that were neglected from the type species description. The present discovery of a new species increases the known diversity of Thai land snails and will support the conservation planning to protect karst biodiversity.